Contamination by parasites of zoonotic importance in fecal samples from Florianópolis Beaches, Santa Catarina State, Brazil - Bricarello, Patrizia Ana; Magagnin, Ellen Antunes; Oliveira, Thailini de; Silva, Alice da; Lima, Lenilza Mattos (Brazilian Journal of Veterinary Research and Animal Science, 2018)
Helminths and protozoa are examples of endoparasites that, during their biological cycles, can alternate between free-life stages and parasitic stages in the environment. Pets, such as dogs and cats, live together with men and play an important role in the society; however, these animals may carry a large number of parasites which, besides showing direct pathogenicity to the host, represent risks to the human health, as is the case of parasitic zoonoses. Public areas like parks, gardens, squares and beaches may offer risks to human users since these environments may contain feces deposited by parasitized dogs. The present study  verified the occurrence of helminth eggs and/or protozoan cysts or oocysts in fecal samples collected from sand strips at the beaches Armação do Pântano do Sul, Campeche and Morro das Pedras, in the south of Florianópolis Island, Santa Catarina State (SC), during the summer period. Pet feces were collected in the 2016/2017 summer season, from December 2016 to February 2017. In the Laboratory of Animal Parasitology (CCA-UFSC), fecal samples were processed based on Willis-Mollay flotation technique and Hoffman sedimentation technique. Samples from all three analyzed beaches were positive for the presence of parasites and fecal material was found along the seashore, sites where people walk freely and barefoot. Of 104 fecal samples collected, 45 (43.27%) were positive for one or more parasites. The greatest prevalence was found in Campeche Beach, which had 72.22% positive samples. Ancylostomids were most prevalent, indicating that cutaneous larva migrans is likely to occur in humans. Other parasites such as Trichuris vulpis, Toxocara spp. and Giardia spp. were also detected in coproparasitological analyses. Based on the results, it was concluded that contamination of the beaches in Florianópolis Island, SC, constitutes a public health problem due to the possibility of zoonosis transmission. These results reinforce the importance of establishing health programs for parasite control and educational programs for elucidating the risks of transmission of these zoonoses to the population, as an attempt to reduce environmental contamination risks at beaches of seaside resorts.